Audit Sistem Informasi Absensi Dingtalk Menggunakan Cobit 5 dengan DSS dan MEA - Syahputri, Haurora Rizki; Zuraidah, Eva (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Information system audits are carried out to identify and ensure that existing system procedures in the company function properly, using Cobit 5 to audit the DingTalk application information system at PT Global Optimus Prime Logistik because a comprehensive audit of the information system has never been carried out and it cannot be confirmed that it is appropriate or not according to company standards. With an information system audit on the DingTalk system running in the company, it is hoped that it can align needs with company goals. The research was collected using quantitative capability analysis. The audit results with the highest score, namely MEA01, received a maturity level of 80.90 with a Largely Achieved achievement score and a GAP score of DSS01.01 with a GAP score of 0.8, DSS01.02 with a GAP score of 1.1, DSS01.03 with a GAP score of 0.6, DSS01. 04 has a GAP value of 0.5, and DSS01.05 has a GAP value of 1.2 from target level 5. Meanwhile, the MEA 01 domain received a Maturity Level of 58.00 with a Largely Achieved achievement value, MEA01.01 has a GAP value of 3.8, MEA01.02 has a GAP value of 3.3, MEA01.03 GAP value of 3.1, MEA01.04 GAP value 2m8, MEA01.05 GAP value 2.5 from target level 5. Analyst GAP results obtained from DSS01 and MEA01 have reached the target level.